PROSEDUR PERTANGGUNGJAWABAN ATAS PERJALANAN DINAS PADA PT KALBE FARMA TBK - Aurelia Putri Salsabila Widyantara (2023)
With the rapid development of the world, professionals in their respective fields are required to keep up with the progress. Business travel for PT. Kalbe Farma, Tbk is an important matter considering that this business travel is closely related to the performance of duties. Referring to the activities of travel conducted by employees or staff of an institution or company in order to fulfill the needs and interests of that institution or company. During the implementation of business travel, several expenses need to be considered, prepared, and incurred, as well as the need for provisions as standards for the budget that will be used during the course of the business travel. This procedure for business travel explains the flow of travel from the creation of task documents, the process of submission and disbursement of advances, to the realization accountability process. Based on the information stated in the discussion regarding the procedure, business travel at PT. Kalbe Farma, Tbk has been conducted in accordance with the provisions and has been highly effective and efficient.